Improving Reach Out and Read Implementation in the NICU - Poindexter, Natasha (My University, 2023)
Neonates in the Neonatal Intensive Care Unit (NICU) are at high risk for neurocognitive and behavioral deficits. Reading to these neonates is shown to improve short- and long-term outcomes. Reach Out and Read (ROR) expanded its reading program to the acute care setting of NICUs in 2018. Expansion to NICUs has proven difficult as evidenced by only eight NICU sites utilizing ROR in the United States. The implementation model of ROR in the NICU designates a medical doctor as the leader of ROR enrollment and education. Surveys were designed to identify the inner workings of the NICU and identify barriers and facilitators to book program implementation. Surveys were sent out to NICU sites that utilize this program, those that utilize additional book programs, and those that do not implement any book program. The data identified bedside registered nurses (RN) as the individual who most often initiated ROR enrollment and did the most education to parents. It is recommended that a ROR unit committee be established as a site liaison role in the ROR implementation model.
Keywords: Reach Out and Read, neonatal intensive care unit, early brain development, survey, program implementation